Regionalne razlike in regionalno planiranje - Černe, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
One of the basic questions, that are remaining unsolved, in spite of long-term theoretical, methodological and practical experiences in and outside planning, is without any doubt question of the nature and signi. cance of regional disparities. In contribution we would like to draw attention to some contradictions, caused by understanding of region, regional development, regional planning and by emphasizing regional disparities as one of those elements, which are unconditionally argumentation for regional planning actions.
Keywords: regionalno planiranje; regionalni razvoj; regije; regionalne razlike; Slovenia; Slovenija